ChemInform Abstract: Direct Access to β‐Fluorinated Aldehydes by Nitrite‐Modified Wacker Oxidation. Issue 47 (3rd November 2016) - Chu, Crystal K.; Ziegler, Daniel T.; Carr, Brian; Wickens, Zachary K.; Grubbs, Robert H.
Abstract: An aldehyde‐selective Wacker‐type oxidation of allylic fluorides proceeds with a nitrite catalyst.